SERIOUS INJURY CLAIMS REJECTED BY THE ROAD ACCIDENT FUND: THE APPEAL PROCESS - M Slabbert; HJ Edeling (Obiter, 2016)
The Road Accident Amendment Act came into effect in 2008. This Act limits the Road Accident Fund’s liability for compensation in respect of claims where serious injuries have been sustained. In the event of the Road Accident Fund rejecting a serious injury claim the appeal process is prescribed by the regulations to the Act. The disputed case has to be referred to an Appeal Tribunal under the auspices of the Health Professions Council of South Africa. The Tribunal faces many challenges despite the fact that the use of the AMA Guides is intended to yield objective and consistent findings.